Restoration of the endemic hermatypic coral Cladocora caespitosa in the Mediterranean Sea: micro-fragmentation and nursery rearing - Cardinale, P.; Danovaro, R. (Frontiers in Environmental Science, 2025)
Cladocora caespitosa is the only reef-building zooxanthellate coral in the Mediterranean Sea. It forms beds of colonies, sporadically aggregating in extensive reef-like structures. The carbonate deposition of C. caespitosa enhances habitat complexity, supports biodiversity, and contributes to carbon sequestration. Anthropogenic pressures have increasingly threatened this species. Due to its decline, the International Union for the Conservation of Nature (IUCN) included C. caespitosa in the endangered species list. Here we exploited the available knowledge on tropical coral reefs to develop a protocol for the propagation of this Mediterranean species. In this preliminary study, we exploited naturally occurring dislodged fragments as donor material and successfully implemented the micro-fragmentation and nursery-rearing techniques on this species, looking forward to future restoration interventions. We reported that micro-fragmented C. caespitosa has high survival and asexual reproduction rates surpassing those of naturally occurring juvenile colonies. We also report that bleached C. caespitosa fragments were able to survive and grow, although at a much lower rate than their unbleached counterparts and recover with the re-establishment of lower temperatures. One year after the start of micro-fragmentation experiment, a survival rate of 89.8% was observed, with all fragments encrusting on their artificial substrates.